PENGARUH LATIHAN LADDER DRILLS TWO FEET EACH SQUARE DAN ICKY SHUFFLE TERHADAP KECEPATAN GERAK - FAJAR IHTIARINI, WAHYU (Jurnal Kesehatan Olahraga, 2016)
ABSTRACT THE EFFECT OF LADDER DRILL TWO EACH SQUARE FEET AND ICKY SHUFFLE TOWARD MOVEMENT SPEED Name: Wahyu Fajar Ihtiarini NIM: 12060484253 Study Program: S-1 Department : Health Education and Recreation Faculty : Faculty of Sport Science Name of Institution : State University of Surabaya Supervisor : Dr. Achmad Widodo, M.Kes Speed is the ability of someone to work on the continuous movement in the same form with the shortest time. The purpose of this research was to know the effect of ladder drill two legs each square and icky shuffle exercise against speed motion. This research used experimental research using pre-test and post-test with 30 samples. The results of the research obtained the average of speed in two feet each square are 4.863 in the pre-test and 4.535 in the post-test. While, the average of speed in icky shuffle test are 5.747 in pre-test and 5.536 in post-test. Based on the homogeneity test, it is obtained that Ftable is more than Fcounting (3.18 > 0.5077) in ladder drill two feet each square data whereas Ftable is more than Fcounting (3.18 > 0.5897) in ladder drill icky shuffle). Based on the normality test of ladder drill two feet each square, the result shows that x2table is more than x2counting (5,991 > 3,455) in the pre-test and (5,991 > 2,291) in the post-test. Besides, on ladder drill icky shuffle, the result shows that x2table is more than x2counting (5,991> 3,461) in the pre-test and (5,991> 2,3115) in the post-test, so the data is normally distributed. The calculation of average difference test on speed before and after exercise by using ladder drill two feet each square results in tcounting -2478 while in ladder drill icky shuffle tcounting -4054. The value of ttable with the significance level of 0.05 by the df = 14 is 2977. Since both are smaller from ttable 2.977, H1 is accepted which means there are differences in speed before and after given treatment. In summary, both ladder drill two feet each square dan ladder drill icky shuffle affect the increasing of the speed. Keywords: drills, ladder drills drill two feet each square and icky shuffle, speed. ABSTRAK PENGARUH LATIHAN LADDER DRILLS TWO FEET EACH SQUARE DAN ICKY SHUFFLE TERHADAP KECEPATAN GERAK Nama : Wahyu Fajar Ihtiarini NIM : 12060484253 Program Studi : S-1 Jurusan : Pendidikan Kesehatan dan Rekreasi Fakultas : Fakultas Ilmu Keolahragaan Nama Lembaga : Universitas Negeri Surabaya Pembimbing : Dr. Achmad Widodo, M.Kes Kecepatan adalah kemampuan seseorang untuk mengerjakan gerakan berkesinambungan dalam bentuk yang sama dengan waktu yang sesingkat-singkatnya. Tujuanpenelitianiniadalahuntuk mengetahui pengaruh latihan ladder drill two feet each square dan icky shuffle terhadap kecepatan gerak. Penelitian ini menggunakan jenis penelitian eksperimen dengan menggunakan pre-test dan post-test. Sampel penelitian ini sebanyak 30 sampel. Hasil penelitian diperoleh rata-rata – rata kecepatan pada pre-test two feet each square sebesar 5,747 dan pada post test sebesar 5,536. Sedangkan hasil rata-rata pre-test icky shuffle sebesar 5,676 dan post-test sebesar5,374 . Berdasarkan uji homogenitas data ladder drill two feet each square diperoleh Ftabel lebih besar dari F hitung (3,18 > 0,5077) sedangkan data ladder drill icky shuffle diperoleh Ftabel lebih besar dari F hitung (3,18 > 0,5897). Berdasarkan uji normalitas data pre test dan post test ladder drill two feet each besar squarediperoleh x2tabel lebih dari x2hitung (5,991 > 3,455) dan post test (5,991 > 2,291),sedangkan pre test dan post test ladder drill icky shuffle diperoleh x2tabel lebih dari x2hitung (5,991 > 3,461) dan post test (5,991 > 2,3115), sehingga data berdistribusi normal. Perhitungan uji perbedaan rata-rata kecepatan sebelum dan sesudah diberi latihan menggunakan ladder drill two feet each square diperoleh thitung -2,478 sedangkan ladder dril icky shuffle thitung -4,054 nilai ttabel dengan taraf signifikansi 0,05 dengan df = 14 adalah 2,977. Karena keduanya lebih kecil dari ttabel 2,977, maka H1 diterima yang berarti terdapat perbedaan kecepatan sebelum dan sesudah diberikan perlakuan. Jadi bentuk latihan ladder drill two feet each square dan ladder drill icky shuffle keduanya memiliki pengaruh terhadap peningkatan kecepatan. Kata kunci : latihan, ladder drills two feet each square dan ladder drill icky shuffle, Kecepatan.